Analisis Pengaruh Gaya Kepemimpinan terhadap Kinerja SPG PD. Sumber Jaya - Teguh Sriwidadi; Oey Charlie (Bina Nusantara University, 2011)
PD Sumber Jaya is a company engaged in the leather goods and accessories retailer that sells Braun Buffel brand which has several stores in Jakarta, Surabaya, and also a number of outlets throughout Indonesia. In each outlet is guarded by several Sales Promotion Girls (SPG). The purpose of this study is to analyze the influence of leadership style on the performance of SPG PD. Sumber Jaya. The method of analysis used in this study is Test Validity, Test Reliability, Mean, Pearson Correlation, and Regression . Data obtained from SPG assessment of managers by filling out the questionnaire that has been provided by using a Likert scale. The results achieved in this research is the leadership style which is run by managers PD. Sumber Jaya is a type of democratic and individual leadership styles have a strong influence of (0.195) or 19.50% and the direction (+) on the performance of SPG PD. Sumber Jaya.Leadership style has a fairly strong relationship (ryx1 = 0.442) on the performance of SPG.